A New Model for Predicting Settlement Within the Influence Area of Shield Construction Based on Dynamic Weight Function and Asymptotic Decay Term - Li, ZongYang; Zhang, Aiqing; Zou, Xin; Du, Zhengxin (Advances in Civil Engineering, 2025)
The settlement prediction of monitoring projects within the affected area of shield construction is a key technical issue in engineering safety control. However, traditional settlement prediction models have significant limitations in terms of complex geological conditions and adaptability of dynamic construction parameters, especially in the lack of long‐term settlement prediction accuracy. In this article, a new settlement prediction model based on dynamic weight function and asymptotic decay term is proposed to address this problem. The dynamic adjustment of the primary and secondary settlement components at different stages was realised, reflecting more accurately the three‐stage characteristics of settlement (acceleration, stabilisation and decay stages). The results show that the progressive decay term proposed in this article effectively solves the problem of too fast decay of subcomponents in the traditional model and significantly improves the accuracy of long‐term settlement prediction by nearly 10%. Through the verification of actual engineering monitoring data, the model in this article is superior to the traditional model double exponential decay model in terms of prediction accuracy and adaptability, especially in the long‐term settlement prediction under complex geological conditions shows significant advantages. The model can provide a more reliable theoretical basis and technical support for the prediction and control of settlement in metro shield construction, which has important engineering application value.